Information Systems, Transformational Leadership, and Organizational Culture on Employee Performance with Moderation of Generational Groups - Anis Fuuadah; Istiatin Istiatin; Siti Maryam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine and analyze the influence of information systems, transformational leadership, and organizational culture on employee performance with generational groups as moderating variables at the Religious Court in the former Surakarta Residency area. This study uses a quantitative approach with descriptive methods. The population in this study were all employees of the Religious Court in the former Surakarta Residency area. Data collection was conducted by distributing questionnaires to respondents who met the research criteria. Data analysis used the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software through outer model testing, inner model testing, hypothesis testing, and Multi Group Analysis (MGA) to examine differences in influence between generational groups. The results of the study indicate that information systems, transformational leadership, and organizational culture have a positive and significant effect on employee performance. This finding indicates that the better the implementation of information systems, the more effective the transformational leadership implemented by leaders, and the stronger the developing organizational culture, the higher the resulting employee performance. The results of the generational group moderation test indicate differences in the strength of influence between generational groups on the relationship between information systems, transformational leadership, and organizational culture on employee performance. Thus, generational characteristics are a factor that needs to be considered in efforts to improve employee performance in the Religious Court environment in the former Surakarta Residency area..